Comparison of Changes in Nasal Skin Sensation After Primary and Revision Rhinoplasty Procedures Using Semmes-Weinstein Monofilament Testing - Akyigit, Abdulvahap; Keles, Erol; Yildirim, Yavuz Sultan Selim; Karlidag, Turgut; Eroglu, Orkun; Kaygusuz, Irfan; Yalcin, Sinasi (Oxford Univ Press Inc, 2021)
Background: Numbness of the nasal skin is one of the most common complications following rhinoplasty. Objectives: The present study investigated postoperative changes in nasal skin sensation among primary and revision rhinoplasty patients and evaluated the recovery outcomes for both groups. Methods: A prospective, randomized blinded study was undertaken involving 100 primary and 34 revision open rhinoplasty patients and 50 volunteers as control group. Semmes-Weinstein monofilament testing was performed on 7 designated nasal points preoperatively and at postoperative months 1, 3, 6, and 12, and the results were evaluated. Results: Among the primary rhinoplasty patients, the change in reduced sensation on pressure to the tip and infratip over time was significant (P<0.001), whereas there was no statistically significant difference for the other points. Among the revision rhinoplasty patients, the change in reduced sensation on pressure to the tip, infratip, and base of columella over time was significant (P<0.001), whereas there was no statistically significant difference at the other points. In a comparison of the revision and primary rhinoplasty patients at all timepoints, a statistically significant reduction in sensation was noted on the application of pressure to all points in the revision patient group (P<0.001). Conclusions: This study found that the sense of touch on pressure returned to normal, aside from at the tip and infratip, by the end of month 12 in primary rhinoplasty patients. The revision rhinoplasty patients, in turn, were observed to have reduced sensation on pressure by the end of month 12, with the greatest reduction at the tip, infratip, and columellar base.
Keywords: Sensibility; Anatomy; Repair